Lymphomatoid granulomatosis: A rare cause of cavitatory lung disease in an HIV positive child1. Issue 2 (12th June 2012) - Gray, Taryn C.; van Wyk, Abraham C.; Goussard, P.; Gie, Robert P.
Abstract We present an unusual cause of lung cavitation and a neck mass in an HIV positive child, initially thought to be tuberculosis. This case report illustrates that the cause for cavitatory lung disease in immunosuppressed children has a large number of possibilities and careful investigation to determine the etiological agent is warranted. Pediatr Pulmonol. 2013; 48:202–205. © 2012 Wiley Periodicals, Inc.